The European Research Infrastructures of the ESFRI Roadmap in Biological and Medical Sciences: status and perspectives - Alessia Calzolari; Arianna Valerio; Francesca Capone; Mariarosaria Napolitano; Marika Villa; Flavia Pricci; Elena Bravo; Filippo Belardelli (Istituto Superiore di Sanità, 2014)
INTRODUCTION. Since 2002, the European Strategy Forum on Research Infrastructures identified the needs for Research Infrastructures (RIs) in Europe in priority fields of scientific research and drafted a strategic document, the ESFRI Roadmap, defining the specific RIs essential to foster European research and economy. The Biological and Medical Sciences RIs (BMS RIs) were developed thanks to the active participation of many institutions in different European member states associated to address the emerging needs in biomedicine and, among these, the Italian National Institute of Health (ISS), in virtue of its role in public health and research, has been specifically involved in the national development and implementation of three RIs: the Biobanking and Biomolecular Resources Research Infrastructure (BBMRI), the European Advanced Translational Research Infrastructure in Medicine (EATRIS) and the European Clinical Research Infrastructures Network (ECRIN). AIM. This article outlines the design and development of these RIs up to the recent achievement of the ERIC status, their importance in the Horizon 2020 programme and their societal and economic potential impact, with special attention to their development and significance in Italy. CONCLUSIONS. The ISS plays a unique role in fostering a coordinated participation of excellence Italian institutes/facilities to different European biomedical RIs, thus contributing to health innovation, healthcare optimization, and healthcare cost containment.